Estimated Age Calculation with Tooth Coronal Index (TCI) Method Using Orthopanthomography in Malang City Population - Putri, Dina Karimah (Indonesian Journal of Legal and Forensic Sciences (IJLFS); Vol 13 No 1 (2023): Indonesian Journal of Legal and Forensic SciencesDO - 10.24843/IJLFS.2023.v13.i01.p02, 2023)
Age estimation is an important aspect in forensics because it plays a role in determining individual identity. In cases of forensic identification of bodies that are difficult to identify visually or in poor condition, radiography is the choice of non-invasive method that can be used for age estimation, one of which is panoramic radiography. The Tooth Coronal Index (TCI) method is one method that can be used to identify a person's biological age through panoramic radiography. The purpose of this study was to compare the chronological age with the biological age obtained from the measurement of the TCI method on the mandibular premolars using panoramic radiography in the Malang City population. TCI measurement was done by measuring the height of the pulp chamber ( Coronal Height ) and the height of the crown of the tooth ( Coronal Pulp Cavity Height ) vertically from the Cemento Enamel Junction (CEJ) on the mandibular premolars. Then the value is entered in the regression equation that has been determined to obtain an estimate of biological age. Then, the results of the estimated biological age are compared with their chronological age. At last, the difference between biological and chronological age is calculated to determine the approximate age. The mean difference between chronological age and biological age was ± 1.32 years and there is no significant difference between the biological age and the chronological age (p value 0.11). TCI method on the mandibular premolars using panoramic radiography can be used to estimate age in Malang City Population.